Vehicle-assisted decapitation: a case report - Hejna, Petr; Havel, Radovan (The American journal of forensic medicine and pathology, 2012)
A rare case of vehicle-assisted suicide in a 40-year-old man is presented. The victim had tied a rope between his neck and a tree and then attempted to drive the vehicle away while seated in the driver's seat.The acceleration of the vehicle resulted in complete decapitation. Injuries to the organs of the man's neck bore vital signs. This, together with blood aspiration into his airways, confirmed that the victim's injuries took place when vital functions of his organism were still preserved. The degree of cervical trauma found in this case was far greater than that in characteristic ligature strangulation or hanging, except in cases where the body has fallen some distance.
Keywords: dospělí; Suicide; Adult; Automobiles; krev; lidé; Blood; automobily; Forensic Pathology; aspirace do dýchacích cest; sebevražda; Decapitation; Acceleration; Male; dekapitace; Respiratory Aspiration; zrychlení; mužské pohlaví; soudní patologie; Humans